2014
DOI: 10.1515/ract-2014-2272
|View full text |Cite
|
Sign up to set email alerts
|

Redox chemistry of Tc(VII)/Tc(IV) in dilute to concentrated NaCl and MgCl2 solutions

Abstract: Redox speciation of Tc in the aqueous phase was further confirmed by solvent extraction. A good agreement is obtained between the experimentally determined Tc redox distribution and thermodynamic calculations based on NEA-TDB (Nuclear Energy Agency, Thermochemical Database) and ionic strength corrections by SIT or Pitzer approaches. These observations indicate that experimental pH c and h values in buffered systems can be considered as reliable parameters to predict the redox behaviour of Tc in dilute to highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Iron oxides and hydroxides are common industrial and environmental materials that can facilitate contaminant reduction and incorporate contaminants into their crystal structure, thereby shielding contaminants from reoxidation. Cr­(VI) reduction and immobilization by ferrous materials has been extensively researched for a variety of environmental conditions, with reducing agent Fe­(II) present in solution , or as a solid. Similar experimental and computational research efforts have investigated Tc­(VII) immobilization, with an emphasis on Tc­(IV) incorporation into magnetite (Fe 3 O 4 ). Magnetite has an inverse spinel structure, (Fe 3+ ) Tet (Fe 2+ Fe 3+ ) Oct O 4 , where octahedral Fe­(III) Oct substitution by metals with similar ionic radii, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxides and hydroxides are common industrial and environmental materials that can facilitate contaminant reduction and incorporate contaminants into their crystal structure, thereby shielding contaminants from reoxidation. Cr­(VI) reduction and immobilization by ferrous materials has been extensively researched for a variety of environmental conditions, with reducing agent Fe­(II) present in solution , or as a solid. Similar experimental and computational research efforts have investigated Tc­(VII) immobilization, with an emphasis on Tc­(IV) incorporation into magnetite (Fe 3 O 4 ). Magnetite has an inverse spinel structure, (Fe 3+ ) Tet (Fe 2+ Fe 3+ ) Oct O 4 , where octahedral Fe­(III) Oct substitution by metals with similar ionic radii, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As pH of the solution greatly affects the extraction of metal ions as the Tc chemistry is very complex in nature, and the speciation of Tc depends signicantly across the pH range. Yalçıntas ¸, E. et al 55 reported the redox nature of Tc(VII)/Tc(IV) within pH range from 2 to 14.6 in solutions of (0.5 M and 5.0 M) NaCl and (0.25 M, 2.0 M, and 4.5 M) MgCl 2 in the presence of reducing agents like Sn(II), Na 2 S 2 O 4 , Fe(II)/Fe(III), and Fe powder. These experimental observations revealed that pH and E h values in a buffered medium could be considered as potential parameters À ions; organic phase: 0.1 M DB18C6 in nitrobenzene (triplicate measurements were done, and the error limit is AE5%).…”
mentioning
confidence: 99%
“…Redox borderline NO 3 − /NO 2 − calculated at I = 0 using thermodynamic data reported in (Puigdomenech and Taxen, 2000). Triangles in figures a and b correspond to experimental data (pH m , E h and [Tc]) reported in (Yalçıntaş et al, 2015) under analogous conditions but absence of nitrate. 2016) and (Guillaumont et al, 2003).…”
Section: Radionuclidementioning
confidence: 99%
“…Redox borderline NO 3 − /NO 2 − calculated at I = 0 using thermodynamic data reported in (Puigdomenech and Taxen, 2000). Yalçıntaş et al, 2015Yalçıntaş et al, , 2016. As a rather hard Lewis acid, the solubility of Tc(IV) can be enhanced by the complexation with strong Lewis bases such as carbonate (Alliot et al, 2009;Eriksen et al, 1992).…”
Section: Radionuclidementioning
confidence: 99%